2012
DOI: 10.1093/ehjci/jes072
|View full text |Cite
|
Sign up to set email alerts
|

Prosthesis/annulus discongruence assessed by three-dimensional transoesophageal echocardiography: A predictor of significant paravalvular aortic regurgitation after transcatheter aortic valve implantation

Abstract: Three-dimensional TOE planimetry of aortic annulus improves the assessment of prosthesis/annulus discongruence and predicts the appearance of significant AR after TAVI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 19 publications
1
31
0
Order By: Relevance
“…Numerous studies have shown the advantages of 3D assessment of the annulus compared with 2D assessment using multiple modalities, including MDCT, 3,5,6,16,20,35,36 3D-TEE, [7][8][9]11,28,37 and cardiac MRI. 16 Cross-sectional 3D-TEE annulus measurements have generally been shown to be smaller than MDCT measurements, 11,23,24,38 and a recent study demonstrated that MDCT overestimated whereas 3D-TEE underestimated in vitro phantom annulus diameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown the advantages of 3D assessment of the annulus compared with 2D assessment using multiple modalities, including MDCT, 3,5,6,16,20,35,36 3D-TEE, [7][8][9]11,28,37 and cardiac MRI. 16 Cross-sectional 3D-TEE annulus measurements have generally been shown to be smaller than MDCT measurements, 11,23,24,38 and a recent study demonstrated that MDCT overestimated whereas 3D-TEE underestimated in vitro phantom annulus diameters.…”
Section: Discussionmentioning
confidence: 99%
“…Both echocardiography [7][8][9][10][11] and multidetector row computed tomography (MDCT) 5,6,9,[12][13][14][15][16][17][18][19] have been used for annular sizing before TAVR and have been shown to be predictive of postimplantation paravalvular aortic regurgitation. 7,8,13,18,20 Because transesophageal echocardiography (TEE) is a relatively safe procedure 21,22 that does not require iodinated contrast and can be used intraprocedurally during TAVR, it is desirable to develop reproducible and accurate 3D-TEE measurements of the aortic valve annulus. Although recent reviews have suggested that 3D-TEE can be used for cross-sectional area and perimeter measurements, 3,23 studies to date have shown clinically significant differences in 3D-TEE and MDCT measurements.…”
mentioning
confidence: 99%
“…Comparing estimates of circular areas of aortic annulus and left ventricular outflow tract (LVOT) using 2D TEE and RT3D TEE and planimetered areas obtained from RT3D TEE, RT3D TEE planimetered annular and LVOT areas showed the smallest underestimation and the best agreement with multislice computed tomography (MSCT) which was used for reference [45]. The clinical importance of superior accuracy of RT3D TEE for measuring aortic annular dimensions has also been demonstrated for predicting the appearance of paravalvular regurgitation after transcatheter aortic valve implantation [46] [47]. Comparing 2D TEE and RT3D TEE estimates of aortic annular area , only mismatch between RT3D TEE planimetered aortic annular area and prosthesis area was found to be an independent predictor of paravalvular regurgitation [46].…”
Section: Transcatheter Closure Of Vsdmentioning
confidence: 93%
“…Echocardiography is also limited by its relatively narrow field of view, which can make it difficult to understand the spatial relationship between the aortic root and surrounding structures. In addition, the accuracy of 2D echocardiographic measurements was found to be limited because of the oval annular shape, and 3DE showed considerably improved accuracy [4,5]. Also, because of the relatively low spatial resolution, 3DE is not ideal for visualization of the coronary arteries, in particular the location of the origin of the left main artery, which is extremely important during pre-TAVR evaluation to prevent the prosthesis from affecting coronary circulation.…”
Section: Themed Article Y Cardiac Imaging and Diagnostic Techniquesmentioning
confidence: 99%